Matematică
alexandru1214
2015-11-14 18:00:45
Efectuati: a) -3a² + a² + ( 5a² - a² ) + 6a² b) 12a³ - 9a³ + 5a³ + ( 16a³ - 14a³) c) (5x²-3x²+9x²)-(21x²-15x²).
Răspunsuri la întrebare
criscristi77
2015-11-14 20:55:11

[latex] it -3a^{2} + a^{2} + (5a^{2} - a^{2} ) + 6a^{2} = -2a^{2} + 4a^{2} + 6a^{2} = 8a^{2} \ \ 12a^{3}-9a^{3}+5a^{3}+(16a^{3}-14a^{3})=8a^{3}+2a^{3}=10a^{3} \ \ (5x^{2}-3x^{2}+9x^{2})-(21x^{2}-15x^{2})=11x^{2}-6x^{2}=5x^{2} [/latex]

misterioasa76
2015-11-14 20:56:26

a) -3a² + a² + ( 5a² - a² ) + 6a² = -2a^2 + 4a^2 +6a^2 = 8a^2 b) 12a³ - 9a³ + 5a³ + ( 16a³ - 14a³) = 3a^3 +5a^3 + 2a^3=10a^3  c) (5x²-3x²+9x²)-(21x²-15x²) = 11x^2 - 6x^2 = 5x^2 

Adăugați un răspuns